Computational modeling of strained alkenes: Choosing the right computational model. Issue 22 (2nd August 2017) - Kekišev, Ott; Burk, Peeter; Järv, Jaak
Abstract: The applicability of 12 different quantum chemical calculation methods, including density functional theory (DFT) and ab initio methods, for describing strained alkenes and modeling their gas‐phase basicities (GB), hydrogenation enthalpies, and double bond geometries was studied for a series of systematically defined compounds R1R2C = CR3R4. The calculated values were compared to experimental data that had been compiled from literature for several compounds within the series. The closest relationship between the computational results and experimental data occurred with the G2MP2 ab initio method. The best DFT method for GB values was M062X and for hydrogenation enthalpies PBEPBE. At the same time, the relative effects of compound structure variations on the calculated values were similar among all 12 of the calculation methods tested. The double bond length was relatively insensitive to the sizes of the R substituents in R1R2C = CR3R4, but the torsion angles changed significantly in response to structural changes to the compounds when none of the groups R1–R4 was hydrogen. Abstract : Ab initio methods G2MP2 and MP2 adequately describe gas‐phase basicities, hydrogenation enthalpies, and double bond geometries of strained alkenes. Among density functional methods M062X and B2PLYP have the best performance. PBEPBE with D3 dispersion correction are found to be good cost‐effective alternative for applications to strained alkenes.